PERFORMANCE ANALYSIS USING BALANCE SCORECARD IN PT TELKOMSEL - Andi Muhammad Sahrul; Jeni Kamase; Tenriwaru Tenriwaru (Universitas Muhammadiyah Makassar, 2021)
This study aims to measure the performance of PT Telkomsel using the balance scorecard approach from a financial and non-financial perspective; customer perspective, internal business process perspective and, growth and learning perspective. This research is a descriptive study using a mixed method approach, namely a combination of qualitative and quantitative research combined with an explonatory design research model, the data sources of this study are primary data in the form of interviews with informants and questionnaires, and secondary data from literature, financial reports, as well as supporting data related to this research. The results showed a decrease in several financial posts due to changes in government regulations and price competition among telecommunications service providers. From the customer perspective, price product has become a complaint of several customers. From the perspective of internal business processes, it shows the fluctuating value of ARPU and operational costs due to these changes. Continuous training has become a complaint of some employees from a growth and learning perspective, but in general PT Telkomsel's performance with the balance scorecard as a performance measurement tool is already very good.